Progressive Spinal and Cerebellar Multifocal Hemangioblastoma in Von Hippel-Lindau Disease: Case Report and Literature Review - TP. Dinh, Hoai; Kato, Yoko; T. Huynh, Huy; L. Mai, Ngoc; Moungkhounsin, Vilatda; V. Le, Canh; N. Nguyen, Tien; V. Nguyen, Lac; D. Tran, Hoang; T. Le, Hieu; T. Nguyen, Minh (Nepal Journal of Neuroscience, 2025)
Although cerebellar hemangioblastoma is histologically benign, it can exhibit malignant clinical behavior during long-term follow-up. This report presents the case of a 51-year-old male with von Hippel-Lindau (VHL) disease, characterized by multifocal hemangioblastomas in the spine and cerebellum, as well as multiple cystic lesions in the kidneys and pancreas. The patient underwent nine surgeries for recurrent cerebellar hemangioblastomas and received cranial radiotherapy for multiple intracranial masses. Additionally, he was diagnosed with and treated for renal cell carcinoma arising from a renal cyst. This case highlights the potential for cerebellar hemangioblastoma recurrence and malignant progression of associated lesions in VHL disease, even after complete resection.